KONSTRUKSI GENDER DALAM KOMUNITAS TATTOART DI KOTA GORONTALO - Abdur Rahman Adi Saputera; Windiyani Yuniarti Tomayahu (Jurnal Studi Gender dan Anak, 2020)
Some of the women often wear clothes that tend to show. Tattoos can make them have a positive impression wherein it makes them feel sexy, cool or attractive in appearance. The reason for using a tattoo is because they like the image on the other hand because they prefer to have an image in their body which is their characteristic in their socializing. The purpose of this study was to determine the gender construction in the Tatoart community in Gorontalo City. The method used in this research is a qualitative method with data collection through observation, interviews, and documentation. The results of the research are; Gender construction in the Tatoart Community as a style to beautify one's appearance. Tattoos are also used as a measure of association, meaning that the more tattoos the woman is assessed for the extent of her association. So that some women admit that the use of tattoos is considered more slang in front of their friends. Women who have tattoos are those who also have playmates who have tattoos, so they are influenced to get tattooed. And some women who have tattoos also reason to put tattoos because of identity. The meaning for each tattoo is different. This depends on the selection of the tattoo motif and the placement of the tattoo on the body. Women put on permanent tattoos, which are tattoos that can last a lifetime on the skin, and for placement, women who are tattooed in Gorontalo City are generally more daring to put it around the body that is not covered to make it easier to show off. is considered positive when the use of tattoos is used as art or decoration that aims to beautify the body or appearance. The self-concept of tattooed women belonging to the Gorontalo Tattooart Community (GTC) is a concept where they act in accordance with the views of themselves and others towards themselves. The tattooed woman, a member of the Gorontalo Tattooart Community (GTC), considers tattooing as an art that everyone is free to wear, and they think that they can learn a lot after using tattoos because of the many negative views from outsiders that make them even stronger individuals in carrying out the day.